Nguyễn Thanh Tâm

Giới thiệu về bản thân

Chào mừng bạn đến với trang cá nhân của Nguyễn Thanh Tâm
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
xếp hạng Ngôi sao 1 ngôi sao 2 ngôi sao 1 Sao chiến thắng
0
(Thường được cập nhật sau 1 giờ!)

''Ant-man'' is a superhero released in 2015 and directed by Peyton reed.The movie is baced on the marvel comics character of the same name and star Pual Rudd as Scott Lang,master thief who becomes the new ''Ant-man'' after being recruiyed by inventor Hank Pym (played by Michael Douglas).Lang must don the ''ant-man'' suit and use his newfound abilites to preven Pym's former protégé,Darren cross(play by corey stoll),from using Pym's technology for evill purposet.With a mix of action,comedy,and heart,''ant-man'' is a thrilling and entertaining add dition to the Mavel Cinematic Universe.

a, \(\dfrac{1}{5}\)+\(\dfrac{4}{5}\):x=0,75

    \(\dfrac{1}{5}\)+\(\dfrac{4}{5}\):x=\(\dfrac{3}{4}\)

         \(\dfrac{4}{5}\):x=\(\dfrac{3}{4}\)-\(\dfrac{1}{5}\)

         \(\dfrac{4}{5}\):x=\(\dfrac{11}{20}\)

             x=\(\dfrac{4}{5}\):\(\dfrac{11}{20}\)

             x=\(\dfrac{16}{11}\)

vậy x=\(\dfrac{16}{11}\)

b, 

                                                                          giải 

       chu vi mảnh vườn hình chữ nhật là

                (5,5+3,75).2=18,5(M)

      số khóm hoa trồng được là

               18,5:\(\dfrac{1}{4}\)=74(khóm hoa)

 vậy trồng được số khóm hoa là 74 khóm hoa

a, \(\dfrac{2}{3}\) .\(\dfrac{5}{\text{4}}\) - \(\dfrac{3}{\text{4}}\).\(\dfrac{2}{3}\)

=\(\dfrac{2}{3}\).(\(\dfrac{5}{\text{4}}\)-\(\dfrac{3}{\text{4}}\))

=\(\dfrac{2}{3}\).\(\dfrac{1}{2}\)

=\(\dfrac{1}{3}\)

b, 2.\(\left(\dfrac{-3}{2}\right)^2\)-\(\dfrac{7}{2}\)

=2.\(\dfrac{3}{2}\)-\(\dfrac{7}{2}\)

=3-\(\dfrac{7}{2}\)

=\(\dfrac{-1}{2}\)

c, \(\dfrac{-3}{4}\).5\(\dfrac{3}{13}\)-0,75.\(\dfrac{36}{13}\)

=\(\dfrac{-3}{4}\).\(\dfrac{68}{13}\)-\(\dfrac{3}{4}\).\(\dfrac{36}{13}\)

=\(\dfrac{-3}{4}\)(\(\dfrac{68}{13}\)+\(\dfrac{36}{13}\))

=\(\dfrac{-3}{4}\).\(\dfrac{104}{13}\)

=\(\dfrac{-78}{13}\)